JANGKI DALAM KARYA SENI LUKIS REALIS KONTEMPORER - WAHONO, Drs. Ariusmedi, M.Sn., Drs. Efrizal, M.Pd. (Universitas Negeri Padang, 2018)
Jangki that formerly close to the community now has begun to disappear and no longer functioned. Society gradually began to leave the community and did not enjoy the characteristics of culture itself. The purpose of making this work is to visualize the jangki that has been eliminated by the community through the works of Contemporary Realist Painting. The method used is 1) elaboration or deepening, this is done directly. 2) synthesis is the concept of phase freelance. 3) over the sketch, the coloring process, until final cultivation in the form of finishing works. 4) exhibition season. The work consisting of 10 works that is 1. Helpless 2. Mass swallowed 3. Rattan 4. Buried Rat Gems 5. Young shoots 6. Tied 7. Cage chicken 8. Sadness 9. nyunjan 10. Doeleo.Kata kunci: tradisi , budaya , kerinci , jangki